Delivering knock your socks off service - Zemke, Ron (American Management Association, 2001)
Create a service advantage with the help of customer service guru Ron Zemke. In practical, easy-to-follow steps, learn trusted techniques and positive approaches that will inspire you to believe in the value of customer care and give you the skills and style to deliver it. This book takes these winning concepts to a new level with interactive features that enable you to turn the Knock Your Socks Off Service advantage to a competitive advantage in your own workplace. You will learn how to: See things from the customer's point of view Meet customer expectations and satisfy their needs Create